Serum Endothelin-1 Level Can Reflect the Degree of Lumbar Degeneration: A Cross-Sectional Study - Uslu, Emine Yildirim; Gulkesen, Arif; Akgol, Gurkan; Alkan, Gokhan; Poyraz, Ahmet Kursad; Ilhan, Necip (Springernature, 2024)
Background Endothelin-1 (ET -1) is an agent closely associated with inflammation and has recently been recognized as a significant factor in degenerative processes. This study aimed to investigate the correlation between serum ET -1 level and radiological and clinical manifestations of lumbar disc herniation (LDH) and intervertebral disc degeneration (IDD) pathologies. Methodology The study was conducted with 50 healthy controls and 50 LDH patients. The pain level of the patients was analyzed with the Visual Analog Scale (VAS), and their functionality was analyzed with the Oswestry Disability Index (ODI). The disc degeneration and disc herniation grades were determined using magnetic resonance imaging. Serum ET -1 levels of the participants were measured using the enzyme -linked immunosorbent assay method. Results ET -1 level was significantly higher in the patient group compared to the controls (p < 0.01). A positive correlation was determined between serum ET -1 level and Pfirrmann grade in the patient group (p < 0.01). No correlation was determined between the MacNab grade, VAS, and ODI scores and ET -1 (p = 0.397, p = 0.137, and p = 0.208, respectively). There was no significant difference between the serum ET -1 levels of the patients with or without neurological deficits (p = 0.312). Conclusions The correlation between the serum ET -1 levels and IDD grade suggested that the former could serve as a biomarker to determine the degree of degeneration in the future. However, further research is required to determine the underlying mechanisms.
Keywords: intervertebral disc degeneration; biomarker; pfirrmann grading; lumbar disc herniation; endothelin-1